Dairy intake after prostate cancer diagnosis in relation to disease‐specific and total mortality. Issue 10 (3rd June 2015) - Yang, Meng; Kenfield, Stacey A.; Van Blarigan, Erin L.; Wilson, Kathryn M.; Batista, Julie L.; Sesso, Howard D.; Ma, Jing; Stampfer, Meir J.; Chavarro, Jorge E.
<x xml:space="preserve">Abstract</x> Information regarding postdiagnostic dairy intake and prostate cancer survival is limited. We evaluated intake of total, high‐fat and low‐fat dairy after prostate cancer diagnosis in relation to disease‐specific and total mortality. We included 926 men from the Physicians' Health Study diagnosed with non‐metastatic prostate cancer between 1982 and 2000 who completed a diet questionnaire a median of 5 years after diagnosis and were followed thereafter for a median of 10 years to assess mortality. Cox proportional hazards regression was used to estimate associations between dairy intake and prostate cancer specific and all‐cause mortality. During 8, 903 person‐years of follow‐up, 333 men died, 56 due to prostate cancer. Men consuming ≥3 servings/day of total dairy products had a 76% higher risk of total mortality and a 141% higher risk of prostate cancer‐specific mortality compared to men who consumed less than 1 dairy product/day (hazard ratio (HR) = 1.76, 95% confidence interval (CI): 1.21, 2.55, ptrend < 0.001 for total mortality; HR = 2.41, 95% CI: 0.96, 6.02, ptrend = 0.04 for prostate cancer‐specific mortality). The association between high‐fat dairy and mortality risk appeared to be stronger than that of low‐fat dairy, but the difference between them was not statistically significant (p for difference = 0.57 for prostate cancer‐specific mortality and 0.56 for total mortality). Among men without metastases when diagnosed, higher intake of dairy foods after prostate cancer diagnosis may be associated with increased prostate cancer‐specific and all‐cause mortality.